Investigating the Role of Hippocampal BDNF in Anxiety Vulnerability Using Classical Eyeblink Conditioning - Janke, Kellie L.; Cominski, Tara P.; Kuzhikandathil, Eldo V.; Servatius, Richard J.; Pang, Kevin C. H. (Frontiers in Psychiatry, 2015)
Dysregulation of brain-derived neurotrophic factor (BDNF), behavioral inhibition temperament (BI), and small hippocampal volume have been linked to anxiety disorders. Individuals with BI show facilitated acquisition of the classically conditioned eyeblink response (CCER) as compared to non-BI individuals, and a similar pattern is seen in an animal model of BI, the Wistar-Kyoto (WKY) rat. The present study examined the role of hippocampal BDNF in the facilitated delay CCER of WKY rats. Consistent with earlier work, acquisition was facilitated in WKY rats compared to the Sprague Dawley (SD) rats. Facilitated acquisition was associated with increased BDNF, TrkB, and Arc mRNA in the dentate gyrus of SD rats, but learning-induced increases in BDNF and Arc mRNA were significantly smaller in WKY rats. To determine whether reduced hippocampal BDNF in WKY rats was a contributing factor for their facilitated CCER, BDNF or saline infusions were given bilaterally into the dentate gyrus region 1 h prior to training. BDNF infusion did not alter the acquisition of SD rats, but significantly dampened the acquisition of CCER in the WKY rats, such that acquisition was similar to SD rats. Together, these results suggest that inherent differences in the BDNF system play a critical role in the facilitated associative learning exhibited by WKY rats, and potentially individuals with BI. Facilitated associative learning may represent a vulnerability factor in the development of anxiety disorders.